Right atrial thrombus and pulmonary thromboembolism related to ovarian hyperstimulation syndrome: A case report and literature review - Amin Sayyadi; Mahsa Mahdavi; Behnam Dalfardi; Fatemeh Karami Robati; Mohsen Shafiepour (Clinical Case Reports)
Abstract A young lady with a history of infertility presented to the hospital with dyspnea and chest pain a few days after ovulation induction. Her manifestations were consistent with ovarian hyperstimulation syndrome (OHSS). Further investigations revealed right atrial thrombus and pulmonary thromboembolism. We successfully managed the condition with conservative therapy.